Analisis Self-Presenting pada Anggota Komunitas Anime Lovers Kebumen - Gigih Syamsul Hidayat; Weni Adityasning Arindawati; Khairul Arief Rahman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the self-presentation of members of the Anime Lovers Kebumen community in the social environment. This study uses a qualitative descriptive method, determining informants using purposive sampling techniques. In its data collection, this study used primary data obtained through in-depth interviews and participatory observations with community members, and secondary data obtained from additional informants and other external sources. The data validity technique in this study uses source triangulation. Based on the social community's view of the stigma of wibu, especially members of the ALK community still tend to be negative in almost all aspects, such as appearance and personality that are seen as strange. This makes members of the ALK community choose to close themselves or as much as possible present themselves as normal people in the social environment, so they use the ALK community as a forum to present themselves as a wibu. When ALK members are in a front stage position or in a social environment, they present themselves as their profession without showing their authority to conform to the norms that apply in the social environment.